2021
DOI: 10.3390/jpm11080775
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Metabolic Syndrome and Obesity-Related Indices and Bone Mineral Density T-Score in Hemodialysis Patients

Abstract: Previous studies have reported inconsistent results regarding the associations between metabolic syndrome (MetS) and obesity-related indices and bone mineral density (BMD). However, no previous studies have reported these associations among hemodialysis (HD) patients. The aims of this study were to investigate associations between MetS and its components and BMD T-score in HD patients and also between obesity-related indices and BMD T-score in HD patients with and without MetS. MetS was defined according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 69 publications
(65 reference statements)
2
12
0
Order By: Relevance
“…Another important finding in the present study is that the waist circumference protected our participants from the risk of osteoporosis. This finding is congruent with a previous study that supported a lower risk of osteoporosis in hemodialysis patients with abdominal obesity [ 16 ]. A higher waist circumference reflects abdominal obesity, which may increase bone density by stimulating bone growth and improving the bones’ weight tolerance [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another important finding in the present study is that the waist circumference protected our participants from the risk of osteoporosis. This finding is congruent with a previous study that supported a lower risk of osteoporosis in hemodialysis patients with abdominal obesity [ 16 ]. A higher waist circumference reflects abdominal obesity, which may increase bone density by stimulating bone growth and improving the bones’ weight tolerance [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…Factors that are associated with osteoporosis in pre-dialysis or hemodialysis patients have been found in previous studies, e.g., being female, being of an older age, and having a low body mass index [ 7 , 14 , 15 ]. Abdominal obesity was found to be a preventable factor for osteoporosis risk in hemodialysis patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These indices have been used as surrogate markers of insulin resistance and central obesity, and they have been shown to be highly correlated with metabolic syndrome and the risk of developing atherosclerotic cardiovascular diseases and diabetes mellitus (DM) [ 19 , 20 , 21 ]. Previous studies have also shown associations between these indices and albuminuria [ 22 ], lung function [ 23 ], osteoporosis [ 24 ], peripheral artery occlusive disease [ 25 ], poor cognitive function [ 26 ], and fatty liver [ 27 ]. Prior studies have also suggested that these obesity-related indices can be used as predictors of hypertension [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though the correlation coefficient was low, the gender difference was significant. The reason remains to be further investigated (Greco et al, 2010 ; Kim et al, 2017 ; Wung et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%